1997
DOI: 10.1136/jnnp.63.4.468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antipsychotic medication on electromyographic responses to transcranial magnetic stimulation of the motor cortex in schizophrenia

Abstract: Objective-To assess the eVect of antidopaminergic antipsychotic medication on the electromyographic (EMG) responses of thenar muscles to transcranial magnetic stimulation (TMS) of the motor cortex in schizophrenic patients. Methods-A group of nine drug naïve schizophrenic patients was compared with a group of nine schizophrenic patients established on neuroleptic medication. Surface EMG recordings were made from the thenar muscles while patients maintained a weak isometric voluntary contraction. TMS was applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
3
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 18 publications
2
36
3
2
Order By: Relevance
“…Although medication may clearly play a role in motor changes in schizophrenia, cMEP latency does not seem to be affected (Davey et al, 1997). However, the silent period after TMS was affected by medication, in that the latency of maximal suppression of the voluntary EMG silent period was increased (Davey et al, 1997). This is in contrast to previous reports in (drug-induced) parkinsonism where the silent period is shortened, so that sampling issues or methodological differences may account for this finding.…”
Section: Investigative Use In Schizophreniacontrasting
confidence: 80%
See 1 more Smart Citation
“…Although medication may clearly play a role in motor changes in schizophrenia, cMEP latency does not seem to be affected (Davey et al, 1997). However, the silent period after TMS was affected by medication, in that the latency of maximal suppression of the voluntary EMG silent period was increased (Davey et al, 1997). This is in contrast to previous reports in (drug-induced) parkinsonism where the silent period is shortened, so that sampling issues or methodological differences may account for this finding.…”
Section: Investigative Use In Schizophreniacontrasting
confidence: 80%
“…Cortical inhibitory processes may be abnormal in this patient group, and in treatment-naïve patients with schizophrenia there appears to be a shortening of latency in compound MEP (cMEP) triggered by TMS over the motor strip (Puri et al, 1996). Although medication may clearly play a role in motor changes in schizophrenia, cMEP latency does not seem to be affected (Davey et al, 1997). However, the silent period after TMS was affected by medication, in that the latency of maximal suppression of the voluntary EMG silent period was increased (Davey et al, 1997).…”
Section: Investigative Use In Schizophreniamentioning
confidence: 87%
“…Puri et al 20 found no differences in CSP duration in unmedicated patients compared with healthy controls. Davey et al 21 found longer CSP duration among medicated patients compared with unmedicated patients. These studies, however, used TMS intensities that were much lower than those conventionally used in most CSP studies.…”
mentioning
confidence: 97%
“…In dieser Arbeit wurden keine signifikanten Differenzen der CSP-Dauer zwischen schizophrenen Patienten und Kontrollen beschrieben. In einer weiteren Untersuchung an einer wiederum kleinen Patientenzahl konnten ebenfalls kein signifikanter Unterschied in der Dauer der CSP, jedoch eine längere initiale Latenz ("onset latency") bei behandelten Patienten gefunden werden [15]. In den letzten Jahren erfolgten dann mehrere Studien, wobei nur Fitzgerald et al [20,21,22] in 3 Untersuchungen konstant eine kürzere CSP bei den Patienten reproduzieren konnten und keinen Einfluss der Medikation (Risperidon und Olanzapin) feststellten.…”
Section: Kortikale Silent Period (Csp)unclassified